Comparison of the relative diagnostic performance of 68Ga-DOTA-IBA and 18F-NaF for the detection of bone metastasis - Deng, Jia; Yang, Jian; Wang, Yingwei; Liu, Guangfu; Chen, Yue (Frontiers in Oncology, 2024)
Purpose We aimed to compare the relative diagnostic efficacy of 68Ga-Labeled DOTA-ibandronic acid (68Ga-DOTA-IBA) to that of18F-NaF PET/CT as a mean of detecting bone metastases in patients with a range of cancer types Methods This study retrospectively enrolled patients with bone metastases associated with various underlying malignancies. All patients underwent both 68Ga-DOTA-IBA and 18F-NaF PET/CT scans. Histopathology and follow-up CT or MRI imaging results were used as reference criteria, with a minimum follow-up period of 3 months. The maximum Standardized Uptake Value (SUVmax) and number of bone metastases were recorded. The Target-Background Ratio (TBR) was calculated along with the detection rate, sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of 68Ga-DOTA-IBA and 18F-NaF PET/CT imaging for overall and partial primary solid tumor bone metastases. Pearson chi-square test, McNemar test, and Kappa test was conducted to assess the correlation and consistency of diagnostic efficiency between the two imaging agents. Receiver Operating Characteristic curve (ROC curve) was performed to compare diagnostic performance and the area under the curve of the two imaging agents, determining optimal critical values for SUVmax and TBR in diagnosing bone metastasis. Differences in SUVmax and TBR values between the two imaging agents for detecting bone metastases were analyzed using the Wilcoxon signed rank test. The difference was statistically significant when P < 0.05 Results A total of 24 patients (13 women and 11 men) were included in this study, with a mean age of 52 (interquartile range, 49-64 years). The detection rate, sensitivity, specificity, PPV, NPV, accuracy, and AUC of 68Ga-DOTA-IBA and 18F-NaF PET/CT for bone metastases were 81%, 90%, 62%, 95%, 43%, 88%, 0.763, and 89%, 99%, 59%, 95%, 89%, 95%, 0.789, respectively. There was no significant difference between the two imaging methods (P < 0.01), and there was a significant correlation (X2=168.43, P < 0.001) and a strong consistency (Kappa=0.774,P < 0.001) between the diagnostic results of the two imaging agents. The SUVmax values of lesions measured by 68Ga-DOTA-IBA and 18F-NaF imaging in 22 patients with bone metastasis were 5.1 ± 5.4 and 19.6 ± 15.1, respectively, with statistically significant differences (P<0.05). The TBR values of the two imaging methods were 5.0 ± 5.0 and 6.7 ± 6.4, respectively, with statistically significant differences (P<0.05). The AUC of the SUVmax of 68Ga-DOTA-IBA and 18F-NaF curves were 0.824 and 0.862, respectively, with no statistically significant difference (P=0.490). No significant difference was found in the AUC of the TBR of 68Ga-DOTA-IBA and 18F-NaF (0.832 vs 0.890; P=0.248). Subgroup analysis showed significant correlation between the two imaging agents in the diagnosis of bone metastases in lung cancer and breast cancer, with consistent diagnostic results. However, in the diagnosis of bone metastases in prostate cancer, there was a significant difference (P<0.001) and lack of consistency (P=0.109) Conclusion The diagnostic efficacy of 68Ga-DOTA-IBA for bone metastasis lesions is comparable to that of 18F-NaF. This finding holds significant clinical importance in terms of diagnosis of bone metastasis and selecting treatment plans for patients with malignant tumors